Pengaruh Faktor Internal dan Faktor Eksternal terhadap Stabilitas Bank Syariah Indonesia - Subakti, Hari; Rokan, M.H, Dr. Mustapa Khamal; Harahap, M.E.I, Muhammad Ikhsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is a quantitative study that analyzes the influence of internal factors (total bank assets, income diversification, and capital buffers) and external factors (gross domestic gross and inflation) on the stability of Islamic banks. This research uses panel data, namely Bank Syariah Indonesia in the 2017-2021 period. The method for explaining this research is panel data regression analysis with Eviews version 9. The results of this study prove that starting from the factors of total assets, income diversification, capital buffers, gross domestic income, and inflation significantly affect the stability of Bank Syariah Indonesia. These results also prove that the independent variables consist of internal factors (bank total assets, income diversification, and capital buffers) and external factors (gross domestic product and inflation) simultaneously influencing the stability of Indonesian Islamic banks. In addition, this study also supports the charter value theory but rejects the too-big-to-fail theory. Keywords : stability, total bank assets, income diversification, capital buffer, gross domestic product, inflation.